Notations - Cage, John 1912-1992 (New York Something Else Press, 1969)
Notations is a book that was edited and compiled by American avant-garde composer John Cage (19121992) with Alison Knowles and first published in 1969 by Something Else Press.[1][2] The book is made up of a large collection of graphical scores, facsimiles of holographs, from the Foundation for Contemporary Performance Arts, with text by 269 composers, which are presented in alphabetical order, with each score allotted equal space, and in which the editor has no more authority than the reader in assigning value to the work.[3] The book includes the manuscript for the Beatles song "The Word" (song lyrics, but no musical notation) from the Rubber Soul album (1965).The text of the book was created using chance procedures to determine which of the 269 composers would be asked to write about their work, and how many words each entry was to consist of. These pieces of writing, which contain from one to sixty-four words, are proceeded by paragraph signs. The typesetting was done by Alison Knowles using chance-derived mixtures of typefaces and sizes. There are also comments by Cage and other writers included throughout the book, typeset using similar procedures.